Looking at the Future, Learning from the Past: Current Activities and Upcoming Goals of the European Paediatric Association, the Union of National European Paediatric Societies and Associations - Massimo Mantovani; Julije Mestrovic; Mehmet Vural; Leyla Namazova-Baranova (Union of pediatricians of Russia, 2020)
.